2023
DOI: 10.1108/jme-08-2022-0104
|View full text |Cite
|
Sign up to set email alerts
|

The role of teachers’ views and attitudes in the academic achievement of Roma students

Abstract: Purpose Inclusive education of Roma students is a priority goal of the European Union. However, synthesising analyses reveal precious little progress scored in this area. This study aims to explore the factors that have affect Roma students’ academic achievement, specifically, whether the views of their teachers have an impact on the performance besides individual and family background factors. Design/methodology/approach A large-sample questionnaire-based research study was conducted in the 2019/2020 academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…As a research tool, a life course interview was applied with structured questions covering the whole life course of the individual, focusing also on the components of the development of resilience. Resilience is understood (similarly to the above-cited research of Rayman and Varga [35], based on Masten's concepts) as the ability to resist difficulties when individuals overcome social disadvantages occurring in their lives and proceed successfully on their educational path. The factors of resilience were identified as the individuals' internal difficulties and personal strengths, as well as the barriers and supportive events and the people surrounding them.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a research tool, a life course interview was applied with structured questions covering the whole life course of the individual, focusing also on the components of the development of resilience. Resilience is understood (similarly to the above-cited research of Rayman and Varga [35], based on Masten's concepts) as the ability to resist difficulties when individuals overcome social disadvantages occurring in their lives and proceed successfully on their educational path. The factors of resilience were identified as the individuals' internal difficulties and personal strengths, as well as the barriers and supportive events and the people surrounding them.…”
Section: Methodsmentioning
confidence: 99%
“…This very low rate is also true for Hungary and it shows a huge gap compared to the non-Roma population. Research demonstrates that a large proportion of successful Roma individuals are characterized by a supportive family background as part of a strong community capital [28], with exemplary relatives [29,30], and the combined presence of ties to the majority society [31][32][33][34][35]. Research comparing Roma and non-Roma students found that Roma students are resilient because they rely on their teachers and community when facing obstacles [36].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The Roma constitute one of the largest ethnic minorities in Europe (O'Nions, 2016) and the largest one in Hungary. Similar to several other ethnic minority groups, Roma students lag behind majority students in terms of academic achievement and educational attainment (Fehérvári, 2023;FRA, 2018;Hajdu et al, 2018;Kertesi and Kézdi, 2011) and receive lower grades from their teachers than majority students, even if they have comparable standardised achievement scores (Kisfalusi et al, 2021).…”
Section: The Context Of the Present Studymentioning
confidence: 97%